FRI0169 First validation of consensus definitions for mri lesions in the sacroiliac joint by the assessments in spondyloarthritis international society (ASAS) mri group. (12th June 2018) - Maksymowych, W.P.; Weber, U.; Pedersen, S.J.; Baraliakos, X.; Machado, P.; Sieper, J.; Poddubnyy, D.; Wichuk, S.; Lambert, R.G.; Østergaard, M.
Abstract : Background: The diversity of MRI lesions in the sacroiliac joints of patients with axial spondyloarthritis (axSpA) has only recently been appreciated and consistent terminology, descriptions, and definitions have not yet been internationally accepted. The ASAS MRI group has generated updated consensus lesion definitions (ASAS_MRI_def n ) and these now require validation in multi-reader exercises to support widespread adoption for clinical practice and research. Objectives: To assess the reliability of detection of active and structural lesions as defined by (ASAS_MRI_def n ) on MRI images from the ASAS Classification Cohort (ASAS-CC) in a multireader ASAS exercise. Methods: ASAS_MRI_def n were recorded in an eCRF that comprises global assessment (lesion present/absent) and detailed scoring (SPARCC SIJ inflammation, SPARCC SIJ structural). MRI images were available in a variety of formats (DICOM (n=175), JPEG(n=71), DICOM film(n=32)) and sequences, axial and semicoronal orientations, from 278 of the 495 cases who had MRI performed in the ASAS-CC. Image quality was considered sufficient to record global data by 6 central readers in all cases. An additional reader assessed only images in DICOM format (n=175). Detailed SPARCC scoring data was based only on assessment of images in DICOM format. Detection of lesions assessed as present/absent by global assessment was analysed using kappa. Reliability of detailed scoring was analysed by intraclass correlation coefficient (ICC). Results: Reliability of detection of active and structural lesions was comparable and somewhat better when DICOM images were evaluated (table 1). The most frequently detected active lesion, subchondral inflammation, was detected to a comparable degree of reliability as the most frequently detected structural lesion, erosion. Fat metaplasia in the joint space (backfill) and ankylosis were also reliably detected despite low frequency of occurrence in this cohort. Mean ICC for detailed scores were BME-0.84, Erosion-0.55, Fatty lesion (any)−0.61, Fatty lesion (>1 cm depth)−0.55, Sclerosis-0.73, Fat metaplasia in joint space-0.36, Ankylosis-0.97, Bone bud-0.07. Conclusions: The reliability of the ASAS_MRI_def n was substantial for the most frequently detected lesions. Disclosure of Interest: None declared